Can we incorporate MRD assessment into clinical practice in AML?. Issue 2 (June 2019) - Ossenkoppele, Gert; Schuurhuis, Gerrit Jan; van de Loosdrecht, Arjan; Cloos, Jacqueline
Abstract: Measurable residual disease (MRD) can be assessed either by flow cytometry or molecular techniques. It has been proven to be highly prognostic in quite a number of prospective clinical studies. The recently published ELN MRD recommendations aim harmonize the approaches to MRD assessment in order to improve its overall quality. The predictive value leading to the usage as a surrogate endpoint for survival which would be instrumental for faster drug approvals has still to be proven. Nevertheless, many AML centers use MRD status to inform treatment.